A standardised FACS assay based on native, receptor transfected cells for the clinical diagnosis and monitoring of β1-adrenergic receptor autoantibodies in human heart disease - Bornholz, Beatrice; Benninghaus, Thomas; Reinke, Yvonne; Felix, Stephan B.; Roggenbuck, Dirk; Jahns-Boivin, Valérie; Jahns, Roland; Boege, Fritz (Clinical chemistry and laboratory medicine, 2016)
: Autoantibodies against β -adrenergic receptors (β AR) that stimulate cardiac cAMP-production play a causal role in the pathogenesis of human heart failure. Patients can be subjected to specific therapies, if the presence of potentially cardio-noxious β AR-autoantibodies is reliably diagnosed. This requires assessment of IgG-interactions with the native β AR because β AR-autoantibodies target a conformational epitope inadequately presented by denatured receptors or linear peptides. Here, we report on a standardised diagnostic procedure for the assessment of β AR-autoantibodies in heart failure patients, which is based on IgG-binding to native human β AR. Good laboratory practice (GLP)-conform measurement of β AR-autoantibodies was based on flow-cytometric quantification of differential IgG-binding to native HT1080 cells overexpressing biofluorescent human β AR or not. Receptor-specific IgG-binding was derived from IgG-related median fluorescence of β AR-positive cells corrected for background staining of β AR-negative cells admixed to each measurement. The slope of IgG binding at two different concentrations was used as measure for the titre/avidity of β1AR-autoantibodies. Sensitivity and specificity of the novel procedure for high β AR-autoantibody levels in dilated cardiomyopathy patients (n=40, NYHA class III-IV) relative to n=40 matched healthy subjects was >90%. It was similar to functional assays considered the gold standard and vastly superior to existing screening-procedures employing fixed cells or linear receptor-peptides as auto-antigenic targets. Inter-assay scatter was 7%–15% and linear dilution recovery was within ±10% of expected values throughout. The novel assay possibly provides a tool to determine true prevalence and clinical impact of β AR-autoantibodies. Furthermore, it may serve as companion diagnostic for therapies specifically directed at β AR-autoantibodies.